Study of the properties of polymer composites – reinforcement based on glass and basalt fibers (Eurasian Scientific Herald, 2022)
Composite fittings are increasingly used in various industries and the economy. The use of such compositions in construction requires a modern engineer to have in-depth knowledge of the choice of materials. In this regard, a comparative analysis of composite reinforcement based on glass and basalt fibers was conducted. Price monitoring of composite fittings from leading local manufacturers was conducted. The main deformation-resistance properties of basalt-plastic and fiberglass reinforcement are determined based on the results of numerous tensile tests of rods. A more efficient and economical design of the anchor sleeve is given in comparison with the recommendations. By many criteria, it was concluded that basalt-reinforced plastic reinforcement was slightly superior to fiberglass.